Accelerator mass-spectrometr SB RAS - Rastigeev, S.A.; Frolov, A.R.; Goncharov, A.D.; Klyuev, V.F.; Konstantinov, E.S.; Kutnykova, L.A.; Parkhomchuk, V.V.; Petrozhitskii, A.V. (Вопросы атомной науки и техники, 2013)
The accelerator mass spectrometer (AMS) created at BINP SB RAS is installed at CCU “Geochronology of the Cenozoic era” for sample dating by the ¹⁴С isotope and for biomedical applications. The most distinguishing fea-tures of BINP AMS is the use of the middle energy separator of ion beams, the magnesium vapors target as a stripper and time-of-flight telescope with thin films for accurate ion selection. Present status of AMS complex and the results of experiments for radiocarbon concentration measurements in test samples are presented.